2008
DOI: 10.1007/s00034-008-9053-8
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Partially Adaptive Concentric Ring Array

Abstract: Concentric ring arrays can provide effective beamforming and achieve frequency invariant beampatterns. For long range signal acquisition, the array has a large number of array elements, and partial adaptation is often necessary to increase tracking ability and reduce computation. The topic of this paper is the study of a partially adaptive concentric ring array for three-dimensional audio signal acquisition. We develop the partially adaptive array through partition matrix formulation, provide the associated ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Partial adaptation reduces the computational complexity of processing a large number of elements present in the fully adaptive beamformers (FABs). Li et al (2008) suggested an element space partially adaptive array in which each sub-array uses the delay-and-sum (DAS) weights (Saff and Kuijlaars 1997). The convergence speed is enhanced in comparison to fully adaptive array and noise power is increased mildly (Ilyas et al 2008;Cioffi and Kailath 1984;Dhiman et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Partial adaptation reduces the computational complexity of processing a large number of elements present in the fully adaptive beamformers (FABs). Li et al (2008) suggested an element space partially adaptive array in which each sub-array uses the delay-and-sum (DAS) weights (Saff and Kuijlaars 1997). The convergence speed is enhanced in comparison to fully adaptive array and noise power is increased mildly (Ilyas et al 2008;Cioffi and Kailath 1984;Dhiman et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…The excitations of the elements of the non-optimized subarray are kept unchanged from their original excitations. In [19][20][21][22][23], various analytical and numerical techniques for array pattern optimization have been suggested, and they are basically based on partially adaptive arrays to simplify the array complexity. In [24], a small number of edge elements on both sides of a linear array are optimized to meet the required radiation patterns with controlled nulls.…”
Section: Introductionmentioning
confidence: 99%